PENGARUH OPTIMALISASI PERAN DOKTER GIGI KECIL DALAM DETEKSI GIGI SEJAK DINI (SIGINI) UNTUK MENURUNKAN ANGKA ORAL HYGIENE INDEX SYMPLIFIED (OHI-S)(Penelitian Dilakukan Pada Siswa SD Se Desa Batuan, Kec. Sukawati, Kabupaten Gianyar) - I Nyoman Gejir; I Gede Surya Kencana; I Nyoman Wirata; Ni Nyoman Dewi Supariani; I G A A P Swastini (Jurnal Kesehatan Gigi (Dental Health Journal), 2020)
To keep the dental and oral cleanliness is one of effort to prevent the dental and oral disease. The objective of this research is to know the influence optimalization role of little dentists in Early Detection of Teeth Program to lower Oral Hygiene Index Simplified score of students in Elementary School in Batuan Villages, Sukawati Sub district, Gianyar Regency in 2019.The research is quasi experimental with  pre and post test design. The research will do June 2019.  The population in this research is all students in Elementary School in Batuan Villages, Sukawati Sub district, Gianyar Regency. This research use 106 respondents. The data will analyze with paired t-test, to  know the influencing  of Early Detection of Teeth Program by  optimalization role of little dentists to lower Oral Hygiene Index Simplified score of students in Elementary School in Batuan Villages, Sukawati Sub district, Gianyar Regency.The results of this research shows that before optimalization role of little dentists in Early Detection of Teeth Program, majority (80 peoples: 75.4%) students with OHI-S in middle criteria, and there are 3 peoples (2.83%) with poor criteria. After optimalization role of little dentists in Early Detection of Teeth Program, majority (79  peoples: 74.53%) students with OHI-S in good criteria, and there is not with poor criteria. The results of analyze with Paired Samples Test shiows that there is influence optimalization role of little dentists in Early Detection of Teeth Program to lower score of OHI-S with the value of significance lower than 0.005.The conclusion of this study is optimalization role of little dentists in Early Detection of Teeth Program has influence to lower score of OHI-S of students in Elementary School in Batuan Villages, Sukawati Sub district, Gianyar Regency in 2019. Based on the results of this study recommend that all the elementary schools need to train the little dentist.